Management of various clinical forms of leukoplakia with diode laser therapy -follow up of 5 cases - Dr..Ruchi Bhuyan,Dr. Basant Choudhary (International Journal of Advanced Science and Technology, 2020)
Objective: To study the application of diode laser in the treatment of oral leukoplakia. Materials &methods: In this study we considered 5 case reports those were having oral leukoplakia which wasconfirmed by biopsy test and treated with diode laser. Results: Diode laser provides painless and anearly healing of wound that produced by the surgery. Healing time period was in between 7th days to 30thdays after the laser treatment and there is no recurrence in between 2 year follow up the study.Conclusions: Diode laser is an effective treatment option to removing the infected tissues in themanagement of oral leukoplakia and also helpful to prevents malignancy.